ITIJAHAT AMNA MAKTABAH FI MALAYSIA NAHW TA'ALUM AL-LUGHAH AL-'ARABIYAH LI AGHRADH KHASHAH - Abdullah, Nurul Shifaah Binti; Eltingari, Salih Mahgoub (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
The concept of teaching Arabic for specific purposes (ASP) is the new concept in teaching Arabic to non-native speakers. This study was intended to look at the Trustees of the global library Dar al-Hikma Islamic University in Malaysia where a class of employees imposed working conditions need to learn Arabic; to make them easier to deal with their clients from the Arabic-speaking countries. Therefore, it was a need for the employees to learn Arabic in specific purpose. The study was conducted through descriptive and analytical approach and the data were obtained through personal interview and made up the sample of nine members. The paper concluded the results of the most important: the desire of Trustees of the Dar al-Hikma library to learn Arabic for the purposes of office, and they see the need to focus on speaking and writing skills.DOI: 10.15408/a.v3i2.4591